Contributions of SMEs to Taxation in Ecuador - Valderrama Barragán, Gloria Angélica (2025)
Small and medium-sized enterprises (SMEs) are essential to Ecuador's economy. The research used a descriptive quantitative approach, surveys were conducted with SME owners to assess their tax compliance and perceptions of the tax system. Data collection was carried out through random sampling by strata, ensuring the representativeness of active companies according to Ecuadorian legislation. The results indicate that the tax commitment of SMEs is influenced by factors due to the complication of the tax system and the scarcity of resources and the perception of the tax burden. The research highlights that many SMEs face significant barriers to meeting their tax obligations, which can result in penalties and affect their financial viability. This suggests that it is crucial to implement policies that simplify administrative processes and facilitate performance, which would not only favor businesses, but also increase tax revenues for the State